SAT0135 What Factors are Associated with Methotrexate Monotherapy in Recent Onset Rheumatoid Arthritis? Results from a UK Nationwide Observational Study (RAMS). (9th June 2015) - Humphreys, J.; Sergeant, J.; Anderson, J.; Barton, A.; Hyrich, K.; Verstappen, S.
Abstract : Background: In the UK, methotrexate (MTX) monotherapy is only recommended in the initial management of patients presenting with RA where there are contraindications to combination therapy, or multiple comorbidities. However it is not clear how frequently and why different treatment strategies are used in routine practice. Objectives: To identify, in a national cohort, the frequency of methotrexate monotherapy and examine factors associated with its prescription. Methods: The Rheumatoid Arthritis Medications Study (RAMS) recruited patients with RA starting MTX for the first time since 2008 across the UK, with symptom duration <2 years. Data, including demographics, comorbidity, medication history, smoking history, CRP, RF, DAS28 and HAQ were recorded at start of therapy. Subsequent medication changes were detailed at 3 and 6 month follow-up. Patients were classified as being on MTX monotherapy if they were not either: (1) currently taking or started on another DMARD within 90 days of methotrexate start date, or (2) currently taking or started on oral steroids (for at least 30 days) within 30 days of methotrexate start date. Univariate and multivariate logistic regression analyses were applied to assess the association between MTX monotherapy and baseline age, gender, disease duration, CRP, RF, HAQ, DAS28, smoking status, comorbidity and year of registration. Results: Of 731 patients included 493 (67%) were prescribed MTX monotherapy (table 1 ). 193 (80%) patients on combination therapy were treated with another DMARD and 48 (20%) with steroids. Older age was associated with increased odds of monotherapy and RF positivity with combination therapy (table 1 ). Conclusions: Despite current UK recommendations, in our study MTX was more commonly prescribed as monotherapy than in combination with other DMARDs. Older patients were more frequently treated with monotherapy; however no association was seen with the presence of multiple comorbidities. Others factors such as patient preference may be contributing to these prescribing practices. Disclosure of Interest: None declared